Disengaging Voters: Do plurality systems discourage the less knowledgeable from voting? - Hobolt, S; Fisher, S; Lessard-Phillips, L; Curtice, J (2008)
A number of studies have found that turnout tends to be lower under plurality rule than when some system of proportional representation is in place. Meanwhile, there is reason to believe that when turnout is lower, it is voters who are less knowledgeable about politics who are particularly less likely to participate. This suggests that turnout is lower under plurality rule because those with weaker motivations to vote are particularly discouraged from voting. We consider whether this is the case and if so, why. We examine four main reasons why the electoral system might influence the relationship between political knowledge and turnout: district competitiveness, mobilization efforts, efficacy, and the size and polarization of the party system. Using data from the Comparative Study of Electoral Systems project, we find that those with low levels of knowledge are indeed particularly less likely to vote under plurality rule. However, why this is the case is more difficult to ascertain.